2007
DOI: 10.1111/j.1398-9995.2006.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of omalizumab in patients with severe persistent allergic asthma

Abstract: This study demonstrates that add-on omalizumab therapy is cost-effective in patients with severe persistent allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 27 publications
0
91
1
2
Order By: Relevance
“…The analysis by Brown et al does use the unit of cost per QALY but has other shortcomings. Although the study used for analysis includes a total of 206 subjects in the omalizumab group, the analysis by Brown et al only includes the 68 subjects who responded to omalizumab, defined as having a 0.5-point or greater improvement in the Mini-AQLQ (Brown et al 16 and Ayres et al 46 ). Thus this analysis is a narrow analysis and does not represent the real-world setting in which omalizumab response cannot be predicted before treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis by Brown et al does use the unit of cost per QALY but has other shortcomings. Although the study used for analysis includes a total of 206 subjects in the omalizumab group, the analysis by Brown et al only includes the 68 subjects who responded to omalizumab, defined as having a 0.5-point or greater improvement in the Mini-AQLQ (Brown et al 16 and Ayres et al 46 ). Thus this analysis is a narrow analysis and does not represent the real-world setting in which omalizumab response cannot be predicted before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that omalizumab is not cost-effective. Another cost-effectiveness analysis by Brown et al 16 suggested that omalizumab is cost-effective; however, this analysis was based on a small open-label trial, and the analysis was limited to subjects who were responsive to omalizumab. This creates a strong bias in favor of omalizumab.…”
mentioning
confidence: 99%
“…The cost-effectiveness of anti-IgE has been appreciated for its indication in severe asthma (1742,1743) but not for rhinitis.…”
Section: Anti-igementioning
confidence: 99%
“…Eight studies compared monotherapy vs monotherapy (38,41,42,45,46,51,56,58). Four studies compared add-on omalizumab vs usual care (39,47,57,60). There was one study over the time period that considered the costs of reliever therapies, but since no health outcome was reported this study was excluded (62).…”
Section: Literature Search Resultsmentioning
confidence: 99%